Point-of-care ultrasound (POCUS) in Norwegian general practice. (2nd April 2020) - Myklestul, Hans-Christian; Skonnord, Trygve; Brekke, Mette
Abstract: Objective: To assess the use of point-of-care ultrasound (POCUS) in Norwegian general practice. Design: Retrospective register study based on general practitioners' (GPs') reimbursement claims. Setting: Norwegian general practice excluding out-of-hours clinics in 2009, 2012 and 2016. Subjects: GPs who scanned patients for a given set of symptoms and medical conditions. Main outcome measures: Number and characteristics of GPs performing POCUS. Number and type of scans carried out. Results: The number of scanning GPs increased from 479 in 2009 to 2078 in 2016. The number of registered scans increased from 8962 to 55921. In 2016, approximately 30% of Norwegian GPs sent at least one reimbursement claim for POCUS. Seven out of 10 GPs did not scan every month. The gender distribution of scanning GPs was equal to that of the total GP population. Male GPs scanned four times more frequent than female GPs. Specialist in family medicine scanned twice as much as non-specialist. The use of POCUS among GPs in different counties varied from 31.6 to 198.5 per 10, 000 citizens. Conclusions: The number of Norwegian GPs using POCUS and the number of scans have increased substantially from 2009 to 2016. The use of the various scans, based on the use of reimbursement claims, have evolved differently. The reasons for this are not known. The low number of scans carried out by most GPs raises a concern when it comes to the quality of the performed scans. KEY POINTS: 30% of Norwegian general practitioners (GPs) used point-of-care ultrasound (POCUS) in 2016. The use of POCUS increased six-fold from 2009 to 2016. Three out of four scanning GPs performed less than 10 scans annually. Male GPs performed 80% of the claimed scans.